Exploring Maternalism: Brigitte Bardot, Baby Seals, and Contemporary Hegemonies of the Female Hero - Frenette, Arielle; Desbiens, Caroline; Christensen, Julia; Gagnon, Justine (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
Imperial tales of heroic exploration have had long-lasting effects on the construction of colonial landscapes and of hegemonies of masculinity centered on whiteness, physical strength, and endurance. This paper examines the renewal of such heroic polar explorer narratives in recent times, and how recurring stories tend to re-create as well as produce new hegemonies around gender and race. Through a case study of the expedition of Brigitte Bardot on the Canadian ice shield in 1977 with the intent of saving baby seals, this paper looks at neocolonial implications of a contemporary polar expedition narrative as told by a female “hero”. We argue that BB’s story is “maternalist” in that it is symbolically benevolent but reaffirms colonial authority on Inuit lands and practices based on a discourse of moral virtue and emotional care. Interestingly, the framing of seal pups as “babies” has constructed the act of sealing as gendered and motherhood as an important standpoint for both anti-sealing activism and Inuit pro-sealing resistance.